Working Capital Management Practices of Small and Medium Enterprises in the Western Region. A Survey of Selected Smes in the Sekondi- Takoradi Metropolis - Pieterson, Anita (2013)
A thesis submitted to the Institute of Distance Learning, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the degree of